The Priangan Batik in the Constellation of Modern Aesthetics - Yan Yan Sunarya; Biranul Anas (ITB Journal Publisher, LPPM ITB, 2014)
A study of the aspect of identity in the aesthetic domain of Priangan Batik, from the old Priangan Batik to the present day Priangan Batik, in relation to the constellation change of its aesthetic elements. It considers various impacts of modernity, enriching batik through its ornaments, themes, colors, composition, techniques, and naming to the characteristics of each of the Priangan Batik production areas. Priangan Batik has also been influenced by other cultures. When its local know-how and spirit are traced back in its various forms and dimensions, we can find a reflection of the aesthetic cultural identity of the Priangan community. It has experienced cultural transformation diachronically as well as synchronically, and at the same time adopted elements from various new cultures, including the modern paradigm as well as commercial culture. In the 20th century, batik activity developed in the following Priangan areas: Ciamis, Tasik, and Garut. The development of batik in these areas has expanded it to incorporate a number of values within the dimensions of meaning, principles, and goals. Also, it has been influenced by the heterogeneity Indonesian culture within the constellation of modern aesthetics.Keywords: constellation; modern aesthetics; Priangan Batik.